The cytoplasmic filaments of the nuclear pore complex are dispensable for selective nuclear protein import - Walther, Tobias C. (The Rockefeller University Press, 2002)
The nuclear pore complex (NPC) mediates bidirectional macromolecular traffic between the nucleus and cytoplasm in eukaryotic cells. Eight filaments project from the NPC into the cytoplasm and are proposed to function in nuclear import. We investigated the localization and function of two nucleoporins on the cytoplasmic face of the NPC, CAN/Nup214 and RanBP2/Nup358. Consistent with previous data, RanBP2 was localized at the cytoplasmic filaments. In contrast, CAN was localized near the cytoplasmic coaxial ring. Unexpectedly, extensive blocking of RanBP2 with gold-conjugated antibodies failed to inhibit nuclear import. Therefore, RanBP2-deficient NPCs were generated by in vitro nuclear assembly in RanBP2-depleted Xenopus egg extracts. NPCs were formed that lacked cytoplasmic filaments, but that retained CAN. These nuclei efficiently imported nuclear localization sequence (NLS) or M9 substrates. NPCs lacking CAN retained RanBP2 and cytoplasmic filaments, and showed a minor NLS import defect. NPCs deficient in both CAN and RanBP2 displayed no cytoplasmic filaments and had a strikingly immature cytoplasmic appearance. However, they showed only a slight reduction in NLS-mediated import, no change in M9-mediated import, and were normal in growth and DNA replication. We conclude that RanBP2 is the major nucleoporin component of the cytoplasmic filaments of the NPC, and that these filaments do not have an essential role in importin α/β– or transportin-dependent import.